Bach1 Inhibition Suppresses Osteoclastogenesis via Reduction of the Signaling via Reactive Oxygen Species by Reinforced Antioxidation - Wada, Satoshi; Kanzaki, Hiroyuki; Katsumata, Yuta; Yamaguchi, Yuuki; Narimiya, Tsuyoshi; Attucks, Otis C.; Nakamura, Yoshiki; Tomonari, Hiroshi (Frontiers in Cell and Developmental Biology, 2020)
Bone destructive diseases such as periodontitis are common worldwide and are caused by excessive osteoclast formation and activation. Receptor activator of nuclear factor-κB ligand (RANKL) is essential factor for osteoclastogenesis. This triggers reactive oxygen species (ROS), which has a key role in intracellular signaling as well exerting cytotoxicity. Cells have protective mechanisms against ROS, such as nuclear factor E2-related factor 2 (Nrf2), which controls the expression of many antioxidant enzyme genes. Conversely, BTB and CNC homology 1 (Bach1), a competitor for Nrf2, transcriptionally represses the expression of anti-oxidant enzymes. Previously, we demonstrated that RANKL induces Bach1 nuclear import and attenuates the expression of Nrf2-mediated antioxidant enzymes, thereby augmenting intracellular ROS signaling and osteoclastogenesis. However, it remains unknown if Bach1 inhibitors attenuate osteoclastogenesis. In this study, we hypothesized that Bach1 inhibition would exert an anti-osteoclastogenic effects via diminishing of intracellular ROS signaling through augmented antioxidation. We used RAW 264.7 cells as osteoclast progenitor cells. Using flow cytometry, we found that Bach1 inhibitors attenuated RANKL-mediated ROS generation, which resulted in the inhibition of osteoclastogenesis. Local injection of a Bach1 inhibitor into the calvaria of male BALB/c mice blocked bone destruction induced by lipopolysaccharide. In conclusion, we demonstrate that Bach1 inhibitor attenuates RANKL-mediated osteoclastogenesis and bone destruction in mice by inducing the expression of Nrf2-regulated antioxidant enzymes that consequently decrease intracellular ROS levels. Bach1 inhibitors have potential in inhibiting bone destructive diseases such as periodontitis, rheumatoid arthritis and osteoporosis.